Pendampingan Peningkatan Kebermanfaatan Pojok Baca Desa sebagai Upaya Menumbuh Kembangkan Minat Baca pada Anak - Fitriyah, Neka; Isnaini, Muhammad; Marliana, Nita (Warta LPM, 2025)
Growing and developing children's interest in reading is the first step in shaping the characteristics and creativity of children in Curug Village, Baros District, Pandeglang Regency. Reading is a necessity in increasing knowledge in this village. A strategy to expand the role of the reading corner is needed to improve children's interest in reading, therefore this mentoring activity aims to increase the usefulness of the village corner to grow and develop reading interest in children. This activity uses a community empowerment method with the Participation Rural Applied model with the basic principles of the method of involvement and involvement of children in all activities. There are four stages of activities applied in this service activity; the introduction stage, needs planning, activity organization, and activity evaluation. The need recognition stage consists of direct observations related to the issue of children's interest in reading. The second plan is to prepare activities and determine media, approaches, and methods. Third, the implementation is the process of assisting children in reading, writing, and listening. Fourth, monitoring activities in the form of periodic monitoring. Fifth, evaluation to analyze the process and quality of activities. The result of this activity is children's interest in reading, creativity, enthusiasm, and courage to explore knowledge is wider. The role and existence of the reading corner are very strategic in growing and developing children's interest in reading and knowledge.